Arms Control in Tiv Division of Benue Province, 1933-1954 - Yusuf Danga, Jamiu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The paper examines arms control in Tiv Division, Benue Province in Colonial Nigeria, 1933-1954. The article explores the various rules and their implications introduced to foster arms control against the background of British aspiration to derive economic surplus and maintain control of ownership and trade of arms in the area. The paper examined the circumstances that made the British appropriate strict control of traditional weapons and tools of the Tiv and how the British sort to exchange these weapons for “modern” ones. From a critical perspective, the paper argued that the strict arm control strategy employed by the colonialist was largely as a result of wrong perceptions of the colonialist on the people in Tiv Division as regard uses and control of arms. The paper concludes that the arms used in the Tiv district were traditional arms. Despite the introduction of firearm into the area, there was no popular embrace of these weapons and tools, this led to the domination of arms trade and arms ownership by non-Tiv people in the Division.